Ultrasonic-assisted binding of canistel (Lucuma nervosa A.DC) seed starch with quercetin - He, Rui; Pan, Yong-gui; Shang, Wen-Ting; Zhong, Geng; Huang, Wu-Yang; Xiang, Dong; Pan, Fei; Zhang, Wei-min (Ultrasonics sonochemistry, 2023)
•Ultrasonic modified starch and quercetin combined was formed non-inclusion complex.•Addition of quercetin could protect the damage of starch granule size by ultrasonic.•Quercetin and starch binding through H-bonds and van der Waals interactions.•Ultrasonic modified and quercetin combined affected starch physicochemical properties. In order to provide a reference for improving the physicochemical properties of starch, the study of starch polyphenol complex interaction has aroused considerable interest. As a common method of starch modification, ultrasound can make starch granules have voids and cracks, and make starch and polyphenols combine more closely. In this research, canistel seed starch was modified by ultrasonic treatment alone or combined with quercetin. The molecular structure, particle characteristics and properties of starch were evaluated. With the increase of ultrasonic temperature, the particle size of the dextrinized starch granules increased, but the addition of quercetin could protect the destruction of starch granule size by ultrasonic; X-ray diffraction and infrared spectra indicated that quercetin was bound to the surface of canistel seed starch through hydrogen bonding, and the complex and the original starch had the same crystal structure and increased crystallinity; by molecular simulation, quercetin bound inside the starch molecular helix preserved the crystalline helical configuration of starch to some extent and inhibited the complete unhelicalization of starch molecules. Meanwhile, hydrogen bonding was the main driving force for the binding of starch molecules to quercetin, and van der Waals interactions also promoted the binding of both. In the physicochemical properties, as the temperature increased after the combination of ultrasonic modified starch combined with quercetin, the solubility, swelling force and apparent viscosity of the compound increased significantly, and it has higher stability and shear resistance.